2016
DOI: 10.1186/s12879-016-1650-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inappropriate empirical antibiotic therapy on mortality in patients with healthcare-associated methicillin-resistant Staphylococcus aureus bacteremia: a propensity-matched analysis

Abstract: BackgroundThe purported value of empirical therapy to cover methicillin-resistant Staphylococcus aureus (MRSA) has been debated for decades. The purpose of this study was to evaluate the effects of inappropriate empirical antibiotic therapy on clinical outcomes in patients with healthcare-associated MRSA bacteremia (HA-MRSAB).MethodsA prospective, multicenter, observational study was conducted in 15 teaching hospitals in the Republic of Korea from February 2010 to July 2011. The study subjects included adult p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Inappropriate EAT was not associated with short-term (2–30 days) mortality, an outcome measure that has been studied intensively. Similar to our findings, several studies have reported that inappropriate EAT was not associated with short-term mortality with the cautions that most of these studies included relatively few patients and investigated either individual microorganisms or groups of microorganisms or only reported in-hospital mortality [ 6 , 11 , 12 , 20 , 49 – 52 ]. Nonetheless, the majority of studies focusing on short-term mortality have shown that inappropriate EAT is associated with all-cause mortality as summarised by two major reviews [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Inappropriate EAT was not associated with short-term (2–30 days) mortality, an outcome measure that has been studied intensively. Similar to our findings, several studies have reported that inappropriate EAT was not associated with short-term mortality with the cautions that most of these studies included relatively few patients and investigated either individual microorganisms or groups of microorganisms or only reported in-hospital mortality [ 6 , 11 , 12 , 20 , 49 – 52 ]. Nonetheless, the majority of studies focusing on short-term mortality have shown that inappropriate EAT is associated with all-cause mortality as summarised by two major reviews [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 89%
“…Antibiotics are therefore given on an empirical basis and early initiation of appropriate empirical antibiotic treatment (EAT) has been associated with markedly improved survival in patients with septic shock [ 5 ]. Nevertheless, existing studies have provided conflicting evidence of the association between appropriate EAT and short-term mortality for bacteraemic patients [ 6 20 ]. It is likely that much of the controversy stems from heterogeneity and inadequacy in study designs, which make the comparisons of EAT and bacteraemia outcomes difficult [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of these drugs is associated with severe side effects (Kumar et al, 2016;Yoon et al, 2016), indicating the need for natural methods of inflammation control. Punicalagin, a large natural polyphenolic compound found in pomegranates, is a traditional medicine reported to…”
Section: Discussionmentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA) remains one of the major multidrug-resistant pathogens responsible for severe infections with high mortality rates ( Stefani et al, 2015 ; Yoon et al, 2016 ; Britt et al, 2017 ). The subset of daptomycin-resistant (DAP R ) S. aureus is of particular concern for the cumulative non-reversible metabolic changes demonstrated in resistant strains and for the difficulty in the treatment of severe infections ( Bayer et al, 2013 ; Reed et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%